2013
DOI: 10.1155/2013/363157
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Reorientation Dynamics of Electrically Assisted Light-Induced Gliding of Nematic Liquid-Crystal Easy Axis

Abstract: The phenomenological torque balance model previously introduced to describe the electrically assisted light-induced gliding is generalized to study the reorientation dynamics of the nematic liquid crystal easy axis at photoaligned azo-dye films under the combined action of in-plane electric field and reorienting UV light linearly polarized at varying polarization azimuth,φp. We systematically examine the general properties of the torque balance model by performing analysising the bifurcations of equilibria at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Then the process of relaxation can be described in the approximation of small and angles, by using the linearized Eq. (9) with the boundary conditions (10)- (12), in which = 0. The required, finite at → +∞, solution for the deviation angles of the director and the moving easy axis looks like .…”
Section: The Fréedericksz Transition Threshold Atmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the process of relaxation can be described in the approximation of small and angles, by using the linearized Eq. (9) with the boundary conditions (10)- (12), in which = 0. The required, finite at → +∞, solution for the deviation angles of the director and the moving easy axis looks like .…”
Section: The Fréedericksz Transition Threshold Atmentioning
confidence: 99%
“…The authors of works [10][11][12] proposed a phenomenological model for the easy axis reorientation at the surface of a polymer substrate under the influence of an electric field, but in the azimuthal direction. The model is based on the phenomenon of NLC molecule adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have shown that if a strong applied torque exists for extended periods of time, the easy axis can slowly rotate, leading to a phenomenon known as easy axis gliding or director gliding [1] (the director is a unit vector characterizing the average molecular orientation of the long axis of the molecules). Director gliding has been observed in lyotropic, thermotropic and nematic LCs with multiple experiments reporting both zenithal and azimuthal gliding [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The processes of NLC director and easy axis reorientations in the polymer substrate plane in a strong ac electric field and the relaxation of a system after the field switching-off were studied experimentally and theoretically in work [8]. The simultaneous action of the ac electric field and polarized light on the NLC director dynamics near the polymer surface preliminarily illuminated with ultraviolet was studied in works [9,10]. In works [8][9][10], the easy axis reorientation was explained in the framework of a scenario that is based on the adsorption of NLC molecules on the substrate surface.…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneous action of the ac electric field and polarized light on the NLC director dynamics near the polymer surface preliminarily illuminated with ultraviolet was studied in works [9,10]. In works [8][9][10], the easy axis reorientation was explained in the framework of a scenario that is based on the adsorption of NLC molecules on the substrate surface. The phenomenological model of the phenomenon, which was proposed in those works, involves the influence of the nematic volume on the easy axis motion, decelerating action of polymer, and viscosity of the easy axis motion.…”
Section: Introductionmentioning
confidence: 99%